Role of phosphorolytic cleavage in cellobiose and cellodextrin metabolism by the ruminal bacterium Prevotella ruminicola. - Lou, J (1996)
In bacteria, cellobiose and cellodextrins are usually degraded by either hydrolytic or phosphorolytic cleavage. Prevotella ruminicola B(1)4 is a noncellulolytic ruminal bacterium which has the ability to utilize the products of cellulose degradation. In this organism, cellobiose hydrolytic cleavage activity was threefold greater than phosphorolytic cleavage activity (113 versus 34 nmol/min/mg of protein), as measured by an enzymatic assay. Cellobiose phosphorylase activity (measured as the release of P(i)) was found in cellobiose-, mannose-, xylose-, lactose-, and cellodextrin-grown cells (> 92 nmol of P(i)/min/mg of protein), but the activity was reduced by more than 74% for cells grown on fructose, L-arabinose, sucrose, maltose, or glucose. A small amount of cellodextrin phosphorylase activity (19 nmol/min/mg of protein) was also detected, and both phosphorylase activities were located in the cytoplasm. Degradation involving phosphorolytic cleavage conserves more metabolic energy than simple hydrolysis, and such degradation is consistent with substrate-limiting conditions such as those often found in the rumen.